MEMBANGUN MOTIVASI BERINVESTASI PADA NEGARA BERKEMBANG - Indrawati, Novy Karmelita; Susilo, Hardi (PT. Media Edutama Nusantara, 2024)
ABSTRACT Investment is a key indication of a country's economy. Western nations with advanced economies have a high level of investment from their populations, while Eastern countries with emerging economies continue to have relatively little investment. Many factors impact investing decisions, including income and predicted profit margins. However, research indicates that raising the wages of permanent employees has little direct impact on investment decisions. Investment decisions are determined by psychological motivation rather than merely financial competence. This study intends to investigate the characteristics that motivate people to invest, particularly in developing nations. Qualitative research conducted through in-depth interviews with workers in several institutions in Malang City, East Java, Indonesia, reveals that government sector workers demand different motives for pension security than the public and private sectors. Understanding the investment motivation of workers on fixed incomes can assist institutions in developing policies that encourage the allocation of income for investment, so boosting the micro and macro economy.